ヒョウショウ シンソウ ドリル ノ カイハツ - 藤井, 理行; フジイ, ヨシユキ; 本山, 秀明; モトヤマ, ヒデアキ; 成田, 英器; ナリタ, ヒデキ; 新堀, 邦夫; シンボリ, クニオ; 東, 信彦; アズマ, ノブヒコ; 田中, 洋一; タナカ, ヨウイチ; et al. (1990)
P(論文) 南極氷床のドーム頂上での深層コア掘削計画(ドーム計画)の準備の一環として, 1988年から掘削装置の開発を進めている。本報告は, 2年間の基礎開発段階における研究と実験の結果をまとめたもので, 今後の実用機開発段階を前にした深層掘削機開発の中間報告である。掘削方式としては, 消費電力が少なく, 装置の規模が小さいエレクトロメカニカル方式を採用することとし, 効率の良いドリルをめざし, 切削チップの輸送・処理・回収機構, 切削機構, アンチトルク機構, センサー信号処理と掘削制御機構など各部の検討, 実験を進めた。特に, 液封型のメカニカルドリルの最も重要な切削チップの処理機構では, A型からE型までの方式を比較実験し, A型とC型が優れた方式であることが分かった。国内および南極での実験を通じ, ドリル主要機構の諸課題が解決され, 実用機開発にめどが立った。 A deep ice coring system, which is to be used a top the Queen Maud Land ice sheet in 1994-1995 with a plan named "Dome Project", has been developed since 1988. A mechanical system was adopted because of its less power consumption and smaller size compared with a thermal system. Experiments were done for mechanisms of ice cutting, chip transportation, chip storage, antitorque, monitoring sensors, and winch control with a 20-m drill experiment tower. Experiments were also done in Antarctica. This is an interim report of the development of the JARE deep ice coring system. departmental bulletin paper